Optimizing Documentation Integrity of Ophthalmic Diagnostic Test Interpretation through Electronic Health Record Clinical Decision Support - Yang, Lydia J.; Kuhn, Molly; Blum, James M.; Pouw, Andrew E. (Applied Clinical Informatics, 2025)
Electronic health records (EHRs) have revolutionized clinical practice, but clinicians and institutions have not yet fully optimized their use. Inconsistent documentation of ophthalmic test results can increase potential medicolegal risks if providers bill for tests without properly documenting clinical interpretations.To address this, we developed and implemented a logic tool in Epic (Epic Systems, Verona, Wisconsin, United States) that prompts clinicians to document diagnostic test interpretations as discrete data before closing the patient chart.We implemented a “Close Encounter Warning” using logic rules to redirect clinicians to the Imaging and Procedures section of the Epic chart for documenting test interpretations. The implementation only allows clinicians to finalize each outpatient encounter's charting as closed if the logic rules confirm that no unsigned test results remain. The logic rules were revised many times to accommodate the unique workflow of the Ophthalmology department and to consider the roles of fellows, residents, and staff who also work with encounter charting. We implemented the initial logic rule on October 23, 21 and the final iteration on February8, 22. To evaluate the impact, we compared the number of closed charts containing unresulted diagnostic tests from October 2017 to December 2024.Before we implemented the logic rules, clinicians closed an average of 897.1 charts per month with unresulted diagnostic images (median: 916, interquartile range [IQR]: 170, 5.78% of all outpatient encounters). After implementation, this number dropped to 8.3 per month (median: 8, IQR: 5.75, 0.05% of all outpatient encounters), a 108% reduction (p < 0.001).The Close Encounter Warning logic rules significantly reduced the number of Imaging and Procedure-type diagnostic tests lacking final attending signatures in the Ophthalmology department. By implementing this EHR change, we successfully minimized potential medicolegal liability for our clinicians and institution.
Keywords: electronic health record; health information management; discrete data; ophthalmology; clinical informatics; clinical operations